Оценка высших производных радиальной дальности для сверхманевренных летательных аппаратов - Радван М. Джавад (НТУ "ХПИ", 2010)
Вирішується завдання оцінювання вищих похідних радіальної дальності при русі надманевреного літального апарата. Розглянута модель руху надманевреного літального апарата. Визначені види рухів, які можуть приводити до виникнення вищих похідних дальності. Методом імітаційного моделювання отримані оцінки рівня вищих похідних дальності для різних умов польоту й характеристик літальних апаратів.

The estimation higher derivatives of radial range at movement of a supermaneuverable aircraft dares. The model of movement of a super maneuverable aircraft is considered. Kinds of movements which can lead to occurrence of the higher derivatives of range are defined. Level of the higher derivatives of range for various flights conditions and aircrafts characteristics is estimated by a method of imitating modelling.
Keywords: аэродинамические схемы; искусственная устойчивость; системы сопровождения; радиолокационные измерители; вектор тяги двигателя